Farmers’ adoption of green prevention and control technology in China: does information awareness matter? - Ruifeng Liu; Jian Wang; Mengling Tian; Yefan Nian; Wei Ren; Hengyun Ma; Fei Liang (Humanities & Social Sciences Communications)
Abstract Green prevention and control technology (GPCT) represents an eco-friendly approach in agriculture, aimed at promoting sustainability by reducing farmers’ excessive use of chemical pesticides. Despite the Chinese government having made a large effort to promote the technology, the farmers’ utilization is still low in China, especially when no financial incentives are provided to farmers. This study took 642 farmer questionnaires in Hua county, China, to analyze the effect of information awareness on farmers’ adoption of GPCT. Our findings indicate that farmers’ information awareness is a significant factor in their decision to adopt GPCT. Furthermore, the underlying mechanisms of the influence of information awareness on farmers’ GPCT adoption have been studied. Mechanism analysis shows that farmers’ information awareness affects the adoption of GPCT mainly through social networks. Farmers’ environmental values significantly reinforce the positive influence of information awareness on GPCT adoption. In addition, the regression results from the sub-sample indicate that information awareness has a more pronounced marginal effect on GPCT adoption for farmers with long years of schooling and larger wheat cultivation areas. These results offer insights for promoting GPCT in developing nations.